2008
DOI: 10.1159/000161055
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of the Clock Drawing Test Performance in Alzheimer’s Disease: A FDG-PET Study

Abstract: Background/Aim: This study aimed to identify the functional neuroanatomical correlates of impaired clock drawing test (CDT) performance in patients with Alzheimer’s disease (AD). Method: The CDT was administered to 71 patients with AD, and regional cerebral glucose metabolism (rCMglc) was measured by positron emission tomography (PET). Correlations between CDT scores and rCMglc were examined on a voxel-by-voxel basis. Results: Significant positive correlations were found between CDT performance and rCMglc in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…These group differences were observed when clocks were scored according to the Rouleau scoring system [41], but were not observed with other methods, reflecting the sensitivity of this system to spatial arrangements among clock features. This finding accords with those of Lee and colleagues [44] and Matsuoka and colleagues [45] in Alzheimer’s disease, who reported that Rouleau scores correlated more strongly than did other-system scores with right-parietal structure (i.e. grey matter volume) and function (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…These group differences were observed when clocks were scored according to the Rouleau scoring system [41], but were not observed with other methods, reflecting the sensitivity of this system to spatial arrangements among clock features. This finding accords with those of Lee and colleagues [44] and Matsuoka and colleagues [45] in Alzheimer’s disease, who reported that Rouleau scores correlated more strongly than did other-system scores with right-parietal structure (i.e. grey matter volume) and function (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…One of the better researched visuoconstructional tasks in AD has been clock drawing. Results of studies addressing clock drawing and AD have yielded somewhat discrepant results, though associations with right parietal (Lee et al, 2008) and right temporal cortex (Cahn-Weiner et al, 1999) have been documented, consistent with the present findings using the ROCF. Clock drawing studies have also implicated the involvement of left temporal regions (Nagahama, Okina, Suzuki, Nabatame, & Matsuda, 2005; Thomann, Toro, Dos Santos, Essig, & Schroder, 2008; Ueda et al, 2002), which was not observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…For example, anchorers compared to non-anchorers had higher local efficiency for the left medial OFC, the right rostral ACC and the right SFG as well as the left temporal gyrus that includes Heschl's gyrus. In general terms, several of these regions were hypothesized to be involved in CDT performance and graphomotor organization more specifically based on previous research in normal and pathological aging (Ino, et al, 2003; Lee, et al, 2008; Matsuoka, et al, 2011; Thomann, Toro, Dos Santos, Essig, & Schroder, 2008; Tranel, et al, 2008). We did not, however, find support for parietal involvement in anchoring behavior; this may be due, in part, to the fact that our local efficiency results may represent a relative advantage for anchorers with respect to the connectivity of neurocircuits responsible for the activation, control, and regulation of visually guided motor acts (Izquierdo, Suda, & Murray, 2004; Koechlin, Ody, & Kouneiher, 2003).…”
Section: 0 Conclusionmentioning
confidence: 99%
“…We further hypothesize that these same individuals will display better executive functioning using independent test measures when compared to ‘non-anchorers’. Given that prefrontal, temporal and parietal regions have been implicated in CDT performance including the organization of spatial information such as the layout of numbers (Ino, Asada, Ito, Kimura, & Fukuyama, 2003; Lee, et al, 2008; Matsuoka, et al, 2011; Parks, et al, 2010; Samton, et al, 2005; Tranel, et al, 2008), we hypothesize that individuals who organize their CDT output (versus those who do not) will also show more efficient neural networks associated with these brain regions.…”
Section: 0 Introductionmentioning
confidence: 99%